AmbieGen at the SBFT 2024 Tool Competition - CPS-UAV Track - Humeniuk, Dmytro; Khomh, Foutse (2024 IEEE/ACM International Workshop on Search-Based and Fuzz Testing (SBFT), 2024)
Simulation based testing of autonomous systems prior to their deployment in the real world is of big importance. AmbieGen is a tool for automatic generation of virtual test cases for autonomous cyber-physical systems (CPS). In the context of SBFT 2024 CPS-UAV tool competition, we adopted it to the generation of scenes with obstacles for testing an unmanned aerial vehicle (UAV) obstacle avoidance system. AmbieGen leverages a genetic algorithm guided by a path planner to prioritize test scenarios to be evaluated in the simulation. It could reveal some critical failures in all the 6 use cases considered in the competition.